State of the Union Addresses - Ford, Gerald R., 1913-2006 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses by Gerald R. Ford" is a compilation of three significant speeches delivered by the 38th President of the United States, Gerald R. Ford, from the mid-1970s. This historical account reflects upon the challenges and policies of the United States during a tumultuous time, encompassing issues such as economic instability, energy dependency, and international relations. The addresses likely span a time frame from the early to late 1970s, focusing on the state of the nation in a period marked by societal change and political unrest. In these addresses, Ford articulates his vision and strategy for navigating the country through crises. He tackles pressing issues such as rising unemployment, soaring inflation, and the need for energy independence. Throughout the speeches, Ford emphasizes a partnership between Congress and the President, calls for a reduction in federal spending, and advocates for tax cuts aimed at boosting the economy. He reflects on America's place in the world and the importance of strong international alliances, while also expressing optimism about the nation$1 (Bs ability to overcome obstacles and restore confidence in the American spirit. Ford's rhetoric combines a candid acknowledgment of challenges with a hopeful outlook on America's future, striving to inspire a collective effort toward rebuilding and progress. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources